2016
DOI: 10.1111/liv.13262
|View full text |Cite
|
Sign up to set email alerts
|

The soluble mannose receptor is released from the liver in cirrhotic patients, but is not associated with bacterial translocation

Abstract: This study showed hepatic soluble mannose receptor excretion with a higher level in the hepatic than the portal vein, though with no associations to bacterial DNA. We observed associations between soluble mannose receptor levels and portal pressure and higher levels in patients with acute variceal bleeding indicating the soluble mannose receptor as a marker of complications of cirrhosis, but not bacterial translocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…As more than 80% of body macrophages reside in the liver, sCD163 levels reflect to a high degree liver macrophage activation, and we have previously demonstrated a gradient across the liver in patients with NAFLD and liver cirrhosis 17,37 . Similar findings have been presented for sMR 30 including a gradient across the liver but without association to bacterial translocation 11 . However, the MR is in addition to macrophages also expressed on endothelial and dendritic cells, and the shedding is most likely caused by proteolytic cleavage 38 and different from sCD163, which is shed by the TACE/ADAM enzyme 34 .…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…As more than 80% of body macrophages reside in the liver, sCD163 levels reflect to a high degree liver macrophage activation, and we have previously demonstrated a gradient across the liver in patients with NAFLD and liver cirrhosis 17,37 . Similar findings have been presented for sMR 30 including a gradient across the liver but without association to bacterial translocation 11 . However, the MR is in addition to macrophages also expressed on endothelial and dendritic cells, and the shedding is most likely caused by proteolytic cleavage 38 and different from sCD163, which is shed by the TACE/ADAM enzyme 34 .…”
Section: Discussionsupporting
confidence: 82%
“…TNF, Il‐6), and immune cells from cirrhotic patients have more pronounced in vivo cytokine production after lipopolysaccharide stimulation compared with controls 29 . Especially, the innate immune system with monocytes and macrophages is involved in this cytokine production, and we showed that the macrophage activation markers sCD163 and sMR are elevated in association with liver disease severity and portal hypertension 10,11,30 . This may suggest that with increasing liver disease severity, there is increased macrophage activation, and when these macrophages are further activated by infection or inflammation, they initiate and/or participate in an exaggerated immune response and cytokine storm leading to systemic inflammation, organ failure, and ACLF.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Regarding occurrence of complications within 12 months, sMR was identified as an independent predictor. In a recent study, Laursen et al assessed levels of sMR in patients scheduled for TIPSS implantation and found that sMR levels were elevated in all patients, but especially in patients with acute variceal bleeding indicating sMR as a marker for cirrhosis complications. Actually, the mannose receptor is expressed not only on macrophages, but also on subsets of dendritic and especially endothelial cells that might be activated in patients with portal hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, sCD206 concentrations predict survival, and plasma levels are significantly higher in patients experiencing cirrhosis complications [79]. Another study in cirrhosis patients found a correlation between portal and hepatic vein sCD206 concentrations and the portal pressure prior to insertion of a transjugular intrahepatic portosystemic shunt (TIPS), and with a gradient across the liver [101]. High concentrations are observed in patients with acute liver injury due to an acetaminophen overdose [99] and highest concentrations are found in patients with alcoholic hepatitis [75,78,96].…”
Section: Scd206 In Liver Diseasesmentioning
confidence: 99%